IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI MELALUI MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN SBDP - Said, Wanda; Jusuf, Harni; Nadjamddin, Asriyati (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2024)
AbstractThis study aims to evaluate the improvement in learning outcomes of second -grade students atSDN 7 Limboto in the subject of Arts, Culture, and Crafts (SBDP). The research methodologyemployed is Classroom Action Research (CAR). The participants are 13 second-grade studentsfrom SDN 7 Limboto, consisting of 10 boys and 3 girls. The investigation is conducted over 2cycles, with each cycle comprising 2 meetings and 4 stages according to the Kemmis and Taggartmodel: planning, action, observation, and reflection. The findings indicate that the implementationof differentiated instruction through the Project-Based Learning model is effective in improvingstudents' learning outcomes in SBDP at SDN 7 Limboto. Data analysis in this study usesdescriptive percentage formulas to assess teacher activity, student activity, and student learningoutcomes. Specifically, there is progressive improvement between cycles, with Cycle I showingteacher activity at 61.9%, student activity at 53.8%, and learning outcomes at 30.7%. In Cycle II,teacher activity increased to 79.3%, student activity to 76.9%, and learning outcomes to 84.6%.Based on these results, it can be concluded that differentiated instruction through the Project -Based Learning model effectively enhances students' learning outcomes in SBDP at SDN 7Limboto.Keywords: Differentiated Learning; Project Based Learning Model; Learning Outcomes.AbstrakPenelitian ini bertujuan untuk mengevaluasi peningkatan hasil belajar siswa kelas II di SDN 7Limboto dalam mata pelajaran Seni, Budaya, dan Prakarya (SBDP). Metode yang digunakanadalah Penelitian Tindakan Kelas (PTK). Subjek penelitian terdiri dari 13 siswa kelas II di SDN 7Limboto, terdiri dari 10 laki-laki dan 3 perempuan. Penelitian dilakukan dalam dua siklus,masing-masing siklus terdiri dari dua pertemuan dan empat tahap sesuai dengan model Kemmisdan Taggart: perencanaan, tindakan, observasi, dan refleksi. Hasil penelitian menunjukkan bahwapenerapan instruksi yang terdifferensiasi melalui model Pembelajaran Berbasis Proyek efektifdalam meningkatkan hasil belajar siswa pada mata pelajaran SBDP di kelas II SDN 7 Limboto.Data dianalisis menggunakan formula persentase deskriptif untuk menilai aktivitas guru, aktivitassiswa, dan hasil belajar siswa. Secara khusus, ada peningkatan progresif antara siklus, di manapada Siklus I, aktivitas guru mencapai 61,9%, aktivitas siswa 53,8%, dan hasil belajar 30,7%,sedangkan pada Siklus II, aktivitas guru meningkat menjadi 79,3%, aktivitas siswa 76,9%, danhasil belajar 84,6%. Dengan demikian, penerapan instruksi terdifferensiasi melalui modelPembelajaran Berbasis Proyek terbukti efektif dalam meningkatkan hasil belajar siswa padapembelajaran SBDP di kelas II SDN 7 Limboto.Kata Kunci: Pembelajaran Berdiferensiasi; Model Project Based Learning; Hasil Belajar.